THE ROLE OF THE BGH AND THE STJ AS COURTS FORMING JUDICIAL PRECEDENTS AND THE UNITY OF LAW IN GERMANY AND BRAZIL - Welsch, Gisele Mazzoni (Revista Eletrônica de Direito Processual, 2025)
The purpose of the present study is the comparative analysis of the role of the German and Brazilian superior courts – specifically, BGH and STJ – from the perspective of promoting the uniformity of jurisprudence. Although there is no model of binding to judicial precedents as a judgment technique in Germany as there is in Brazil, in CPC/15, the commitment to the uniformity of jurisprudence permeates the German legal system, including in civil procedure. In this sense, see, for example, the procedural provision of the Revision appeal, which has as admissibility requirements the need for uniformity of understanding on a given matter (Sicherung einer einheitlichen Rechtsprechung) and the preservation of legal certainty (Rechtssicherheit). They both grant the decisions of the BGH (Bundesgerichtshof) authority and compliance with the system in general, with the court exercising an important prospective/forward-looking function. In order to seek an effective contribution to a better and more qualified jurisprudence by the Brazilian Superior Court of Justice, we will highlight the influences of the German civil process for the formation and development of the Brazilian civil procedure. Then, we will move on to the analysis of the common approaches and challenges between the two systems, through the approach of the dogma and doctrine of both countries. To this end, the study of the evolution of the main legislative reforms to the current panorama will be of fundamental value. In the end, we will confront the roles and procedures adopted by the BGH and the STJ as precedent cuts committed to the promotion of development and unity of the law. The aim will be to contribute to the better functioning of the Brazilian Superior Court, based on the German paradigm.